2018
DOI: 10.22159/ijpps.2018v10i6.26186
|View full text |Cite
|
Sign up to set email alerts
|

Pill Burden, Drug Class Distribution and Financial Burden for Buying Medicines in Different Modalities of Chronic Kidney Disease Patients: Cross-Sectional Study

Abstract: Objective: The objective of the study was to assess the pill burden (PB), drug class distribution and financial burden for buying medicines in different treatment modalities of chronic kidney disease (CKD) patients.Methods: A prospective, cross-sectional study was performed in 244 CKD patients and they were divided into 4 groups as follows: pre-dialysis patients (stages 1-5) as group 1, hemodialysis (HD) patients as group 2, peritoneal dialysis (PD) patients as group 3 and renal transplant recipient (RTR) pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, coadministration of MFTA caused marked histological protection on tissue injuries including tubular necrosis, capillary congestion, and epithelial desquamation against APAP administration in Group 3. Cirevalli et al suggested that CKD patient with low-income also against the provision of various drugs to reduce the financial burden on pharmaceutical costs not only for the patient but also to caregivers to their family [32].…”
Section: Parameters Groupsmentioning
confidence: 99%
“…However, coadministration of MFTA caused marked histological protection on tissue injuries including tubular necrosis, capillary congestion, and epithelial desquamation against APAP administration in Group 3. Cirevalli et al suggested that CKD patient with low-income also against the provision of various drugs to reduce the financial burden on pharmaceutical costs not only for the patient but also to caregivers to their family [32].…”
Section: Parameters Groupsmentioning
confidence: 99%
“…Six were cross-sectional studies [ 14–16 , 19 , 21 , 22 ], one was a prospective cohort study [ 17 ], two were retrospective cohort studies [ 20 , 23 ], and one was an intervention cohort study [ 18 ]. One study was published in 2014 [ 21 ], one in 2017 [ 22 ], two in 2018 [ 14 , 15 ], one in 2019 [ 17 ], four in 2021 [ 18–20 , 23 ], and one most recently in 2023 [ 16 ]. One was from the Middle East [ 16 ], four from Asia [ 14 , 15 , 18 , 22 ], three from Europe [ 17 , 21 , 23 ], one from North America [ 20 ], and one from Australia [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study was published in 2014 [ 21 ], one in 2017 [ 22 ], two in 2018 [ 14 , 15 ], one in 2019 [ 17 ], four in 2021 [ 18–20 , 23 ], and one most recently in 2023 [ 16 ]. One was from the Middle East [ 16 ], four from Asia [ 14 , 15 , 18 , 22 ], three from Europe [ 17 , 21 , 23 ], one from North America [ 20 ], and one from Australia [ 19 ]. The smallest study included 150 patients [ 18 ], and the largest study included 27,573 patients [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations